Запровадження інноваційних технологій управління репутацією органів місцевого самоврядування : теорія та практика - Тарасенко, Т. М. (My University, 2022)
У статті розкрито нові можливості для розвитку технологій управління репутацією органів місцевого самоврядування у вимірі парадигми відповідального управління та цифровізації суспільно-владних відносин

The article reveals growing opportunities for the development of technologies for local authorities reputation management within the paradigm of responsible management and digitalization of public relations. It details the importance of activity forecasting, development of forms and methods of activity evaluation, strategic communications for local authorities' reputation management
Іntroduction of innovative technologies of local authorities' reputation management: theory and practice
Keywords: місцеве самоврядування; управління репутацією; репутаційне лідерство; моральна репутація; е-репутація; добра електронна репутація; цифрове спілкування; local authorities; reputation management; reputation leadership; moral reputation; e-reputation; good electronic reputation; digital communication